The Analisa Pengaruh Variasi Waktu Penahanan Panas Dengan Proses Normalizing Pada Baja ST 41 Terhadap Kekerasan Dan Struktur Mikro: Effect Of Time On Strength And Elements In ST 41 Steel - Budiman Budiman (LPPM Universitas Merdeka Madiun, 2022)
The normalizing heat treatment process was carried out on ST 41 steel, a medium carbon type steel at 850°C heating with variations in holding time of 15 minutes, 20 minutes and 25 minutes with air cooling media. This study determines the hardness and microstructure variations in holding time using air cooling media. The result of this study indicates that the (holding time) factor effect the hardness value, the indentation trace's depth value, and the research specimen's microstructure. The first specimen using a holding time of 15 minutes has a hardness value of 68, 25 HRB with an indentation depth of 0,063 mm. The specimen with a holding time of 20 minutes has a hardness value of 70 HRB with an indentation depth 0,058 mm, and a specimen with a holding time 25 minutes has a hardness value of 68 HRB with an indentation depth of 0,063 mm. The hardness test result found that the specimens with variations in holding time 25 minutes had a smaller hardness value and a deeper depth than variations in holding time of 15 minutes and 20 minutes. Furthermore in the microstructure of specimens with a holding time of 25 minutes, the ferrite phase was more dominant than specimens with holding time of 15 minutes and 20 minutes. The phase that appeared at the holding time of 25 minutes was 80,367 % ferrite phase and 19,633 % pearlite phase. So at a holding time of 25 minutes, the ferrite phase is more dominant, so the hardness value of ST 41 steel decreases.